Model code for "Constraining nucleation, condensation, and chemistry in oxidation flow reactors using size-distribution measurements and aerosol microphysical modelling" - Hodshire, Anna; Bian, Qijing; Jimenez, Jose; Pierce, Jeffrey (Colorado State University. Libraries, 2018)
Oxidation flow reactors (OFRs) allow the concentration of a given atmospheric oxidant to be increased beyond ambient levels in order to study secondary organic aerosol (SOA) formation and aging over varying periods of equivalent aging by that oxidant. Previous studies have used these reactors to determine the bulk OA mass and chemical evolution. To our knowledge, no OFR study has focused on the interpretation of the evolving aerosol size distributions. In this study, we use size distribution measurements of the OFR and an aerosol microphysics model to learn about size-dependent processes in the OFR. Specifically, we use OFR exposures between 0.09–0.9 equivalent days of OH aging from the 2011 BEACHON-RoMBAS and the GoAmazon2014/5 field campaigns. We use simulations in the TOMAS (TwO-Moment Aerosol Sectional) microphysics box model to constrain the following parameters in the OFR: (1) the rate constant of gas-phase functionalization reactions of organic compounds with OH, (2) the rate constant of gas-phase fragmentation reactions of organic compounds with OH, (3) the reactive uptake coefficient for heterogeneous fragmentation reactions with OH, (4) the nucleation rate constants for three different nucleation schemes, and (5) an effective accommodation coefficient that accounts for possible particle diffusion limitations of particles larger than 60nm in diameter. We find the best model-to-measurement agreement when the accommodation coefficient of the larger particles (Dp>60nm) was 0.1 or lower (with an accommodation coefficient of 1 for smaller particles), which suggests a diffusion limitation in the larger particles. When using these low accommodation-coefficient values, the model agrees with measurements when using a published H2SO4-organics nucleation mechanism and previously published values of rate constants for gas-phase oxidation reactions. Further, gas-phase fragmentation was found to have a significant impact upon the size distribution, and including fragmentation was necessary for accurately simulating the distributions in the OFR. The model was insensitive to the value of the reactive uptake coefficient on these aging timescales. Monoterpenes and isoprene could explain 24–95% of the observed change in total volume of aerosol in the OFR, with ambient semivolatile and intermediate-volatility organic compounds (S/IVOCs) appearing to explain the remainder of the change in total volume. These results provide support to the mass-based findings of previous OFR studies, give insight to important size-distribution dynamics in the OFR, and enable the design of future OFR studies focused on new particle formation and/or microphysical processes.
The first author (Anna Hodshire) is associated with Colorado State University. All other author affiliations are listed in the published paper, available in the journal 'Atmospheric Chemistry and Physics' under Hodshire et al. (2018).
For those not working in python, .csv versions of the .npz files are also included.
This is the FORTRAN code used for the TOMAS model used in this work. Included are all FORTRAN files needed, a readme file, and a python script and 2 data files (as .npz files) with initial conditions. 2 more .npz data files contain the initial ambient and final OFR size distribution for comparison. The python script and .npz files can be used to run the model for the 0.82 eq. day exposure case discussed in this paper.
Department of Atmospheric Science
Keywords: aerosol; aerosol microphysics; oxidation flow reactor; condensation; aerosol growth; coagulation; nucleation; GoAmazon2014/15; BEACHON-RoMBAS; aerosol modeling